PROBLEMATIKA GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA DI SEKOLAH DASAR - Diva Aulia Aktivana; Ela Hayati; Salsabilla Suci Attalia; Sofyan Iskandar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the paradigm shift from the previous curriculum to the Merdeka Curriculum which brings fundamental changes in the learning approach. Unlike the previous curriculum, which was more structured and centralized, the Merdeka Curriculum emphasizes student-centered, flexible, and contextual learning. This paradigm shift requires teachers to change the way they plan, implement, and evaluate learning. This study examines the problems of teachers in implementing the independent curriculum in elementary schools. The research aims to analyze the problems of teachers in implementing the independent curriculum in elementary schools. This research uses a qualitative approach with library research techniques through a structured study of scientific literature, academic journals, and other relevant sources. The results showed that there were still teacher problems in implementing the independent curriculum in elementary schools